"When Righteousness and Bliss Can Kiss": Working with Our Inner Opposites. (2nd October 2019) - Wesley, Deborah
Abstract : The problem of conflicting energies and desires is basic to human beings. Starting with earliest childhood, whenever some instinctual impulses and feelings are forbidden or unacceptable, they become unconscious. Thus, a part of the personality is lost to us, expressed only in projection onto others. Gaining psychological wholeness then requires the hard work of becoming conscious of these unconscious parts of oneself, and of accepting them.